2016
DOI: 10.5603/gp.2016.0023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship, social support, and personality as psychosocial determinants of the risk for postpartum blues

Abstract: Objectives: The purpose of the study was to identify factors increasing or decreasing the risk for postpartum blues. Material and methods:A total of 101 women in their first week postpartum were included in the study. The Edinburgh Postnatal Depression Scale, questions concerning their medical and social status, and psychological tests (the Neo-Five Factor Personality Inventory NEO-FFI, the Mieczysław Plopa and Jan Rostowski Marriage Questionnaire, and the Berlin Social Support Scales) were used.Results: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
4
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 12 publications
6
34
4
19
Order By: Relevance
“…In the study, we found that most of the sociodemographic factors were not associated with postpartum mood disorders, which is consistent with the literature [1,5,9,13]. No consistent relationship was found between these disorders and the type of relationship, which is contrary to some reports [1,5,7,17].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In the study, we found that most of the sociodemographic factors were not associated with postpartum mood disorders, which is consistent with the literature [1,5,9,13]. No consistent relationship was found between these disorders and the type of relationship, which is contrary to some reports [1,5,7,17].…”
Section: Discussioncontrasting
confidence: 55%
“…No consistent relationship was found between these disorders and the type of relationship, which is contrary to some reports [1,5,7,17]. The much larger group of patients (over five times) allowed us to verify our previous results, where we included the risk factors of extraversion, quality of sleep, and the need for social support [9]. Moreover, the influence of social support was indicated [5,9,18,19].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Послеродовый блюз проявляется психоэмоциональной лабильно-стью, снижением настроения и беспричинной плаксивостью, раздражительностью. Беби-блюз не считается патологическим течением послеродового периода, развивается в резуль-тате гормональных изменений в организме родильницы, однако он может быть фактором риска развития послеродовой депрессии или тревожных расстройств [9,10].…”
Section: Introductionunclassified
“…Основной причиной формирования депрес-сии считаются гормональные изменения в те-чение беременности, во время родоразреше-ния и в послеродовом периоде [11,12]. Также в патогенезе развития депрессии задействова-ны психологические, физические, социальные и акушерские причины [2,10,13]. Кроме этого, одной из причин развития ПРД может быть пе-ренесенная интенсивная боль и стресс во время родоразрешения.…”
Section: Introductionunclassified